Inclusive Pedagogical Practices Within Tufts University Classrooms - Rahman, Shariqa M. (Tufts Archival Research Center, 2023)
This senior honors thesis assesses Tufts' promises of equity within the parameters of a University classroom through an examination of professors' pedagogical practices across the Humanities/Social Science and Natural Science departments.; Thesis (B.S.)--Tufts University, 2023.; Submitted to the Dept. of Sociology.